Factors influencing older adults’ acceptance of voice assistants - Cao, Xiancai; Zhang, Hao; Zhou, Bolin; Wang, Dahua; Cui, Chenhong; Bai, Xuejun (Frontiers in Psychology, 2024)
Voice assistants (VAs) have the potential to uphold and enhance the quality of life for older adults. However, the extent to which older adults accept and benefit from VAs may be relatively modest. This study developed a comprehensive model combined with product and personal characteristics to explain the acceptance of VAs among older adults, using semi-structured interviews (Study 1) and questionnaires (Study 2). Results revealed that in terms of product characteristics, perceived usefulness and perceived enjoyment significantly affect behavior intention. Regarding personal characteristics of older adults, technological self-efficacy and dispositional resistance to change significantly affect behavior intention. However, no direct impact of perceived ease of use and perceived trust on behavior intention. Additionally, perceived enjoyment influenced both perceived ease of use and perceived usefulness. Results suggested the significant role of some unique personal characteristics and developed a new model to predict the acceptance of VAs among older adults.